Nusantara Nature Conservation Foundation's Efforts to Mitigate the Impact of Global Warming Through Mangrove Forest Conservation in Berau in 2018-2022 - Yaser, Muhammad Zayyan; Sagena, Uni; Aftah, Chairul (Research Horizon, 2024)
This research aims to see and describe the efforts of the Indonesian Nature Conservation Foundation in dealing with global warming through mangroves in Berau in 2010-2019, using the concept of Conservation and Global Warming. The data analysis technique used is a qualitative technique. The research results show that the efforts made by the Nusantara Nature Conservation Foundation in dealing with global warming are by planting every 2 years, monitoring mangroves that have developed, providing education to communities around the mangrove ecosystem. This research uses descriptive research using data collection techniques through primary and secondary data in the form of interviews, journals, books, articles and information from official websites. Nusantara Nature Conservation Foundation (Yayasan Konservasi Alam Nusantara/YKAN) (Pratiknjo et al., 2023). Efforts to mitigate the impact of global warming are in collaboration with KKP3K-KPDS, implementing programs in the Berau region that have more of an impact on the economic sector than ecology itself. This can be seen from the achievements of each program which has produced new alternative income for the people in the Berau region, while the impact of global warming itself is still being felt, marked by the increasing temperature changes felt.